PARTISIPASI MASYARAKAT DALAM UPAYA PELESTARIAN EKOSISTEM MANGROVE DI DESA BAGAN PERCUT KECAMATAN PERCUT SEI TUAN KABUPATEN DELI SERDANG, SUMATERA UTARA - Wanda Nelwita Damayani; Ruth Ellyana Ganda Ganda; Meilinda Suriani Harefa; Ihda Anisa (Geography Education Study Program, Universitas Samudra, 2023)
Mangrove ecosystem is the main habitat in the coastal areas of Indonesia. Bagan Percut Village is one of the villages in Percut Sei Tuan District which has a mangrove ecosystem. The purpose of this study is to provide information and an overview of community participation in the conservation of mangrove ecosystems in Bagan Percut Village, Percut Sei Tuan District, Deli Serdang Regency. (2) In mangrove ecosystem conservation activities carried out by the government and community institutions involving the community, the activities carried out are planting mangrove seedlings, providing free seeds, and socializing the mangrove ecosystem. (3) the community routinely conducts mutual cooperation every week for mangrove conservation. (4) In the maintenance of mangrove ecosystems in Bagan Percut Village, Percut Sei Tuan District, Deli Serdang Regency. communities and community groups play a role or supervise the preservation of the mangrove ecosystem.